Dosis de compost protowallpa en el desarrollo vegetativo y rendimiento de Moringa oleífera. Loreto, Perú - Bardales Fasabi, Jorge Alberto (2025)
The use of compost in forage fertilization in the Amazon region is one of the soil- and environmentally friendly alternatives and the National University of the Peruvian Amazon through the Faculty of Agronomy leads the research where the following research is presented: PROTOWALLPA COMPOST DOSE IN VEGETATIVE DEVELOPMENT AND YIELD OF Moringa oleífera. LORETO, PERU. With a completely randomized block design with four treatments and four repetitions, where the treatments under evaluation were T0 (0 tons Protowallpa compost / ha) as a control, T1 (10 tons Protowallpa compost / ha), T2 (20 tons Protowallpa compost / ha) and T3 (30 tons Protowallpa compost / ha), It is concluded that with treatment T3 (30 tons of Protowallpa compost / ha) in the dependent variables at 60 days it has positive or increasing growth at the highest dose of fertilizer. In height 1.57 meters, in green matter 1.60 kilos per square meter, dry matter 0.31 kilos per square meter. In percentage of coverage of 87.43% in treatment T3 (30 tons of Protowallpa compost/ha). Regarding the weight of leaves and stems the following was achieved: 0.82 and 0.79 kilos per square meter. In yield, treatment T3 (30 tons of Protowallpa compost/ha) had a yield of 16,000 kilos per hectare.